STUDI PARTISIPASI PEMILIH PADA PEMILIHAN UMUM KEPALA DAERAH DI KABUPATEN BIMA TAHUN 2020 - Alfisahrin, Alfisahrin; Arafat, Yaser (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2024)
Elections are an important indicator for strengthening the consolidation of political democracy at the local level. The higher the level of voter participation in local elections, the better the quality of citizens' political education. Public participation is very important in maintaining the quality of democracy as well as determining the quality of regional heads produced through honest and fair direct elections. through honest and fair direct elections. This study aims to determine the level of voter participation in the 2020 Bima Regency Regional Head General Election (PILKADA). This research is a library research using a statute approach, concept approach, and historical approach. The data collection technique used is through literature study. Reviewing and studying various literature that discusses the concept of voter participation from various sources such as the General Election Law, books, General Election Commission (KPU) regulations, general election documents at the Regional General Election Commission (KPUD) of Bima Regency. The analysis used used a descriptive qualitative approach. The results of this study are then narrated based on existing data, that voter participation in the 2015 and 2020 Bima Regency PILKADA has increased significantly, the 2015 PILKADA was 70.18% in 2020 at 82%, this shows that the 2020 PILKADA has a high level of voter awareness and political education is quite good.